1990
DOI: 10.1007/bf00006354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydropower peaking flow fluctuations on community structure and feeding guilds of invertebrates colonizing artificial substrates in a large impounded river

Abstract: Artificial substrates were used to monitor the invertebrate communities below a power peaking impoundment and a flow re-regulating impoundment on the Missouri River on northeastern Nebraska, USA. Invertebrate communities on shallow samplers subjected to exposure from diel fluctuations in flow averaged 3 taxa per sampler and 91 organisms per square meter. In the absence of diel fluctuations, number of taxa per sampler increased to 12 and mean densities increased to 743 per square meter. Fluctuating discharges h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 27 publications
3
32
1
1
Order By: Relevance
“…Increased Hydropsychidae density with increased flow fluctuations in the wet season confirms the results of Elliott (1968), Troelstrup and Hergenrader (1990), and Boon (1993). Unlike Hydropsychidae, Simuliidae densities were reduced with increased flow fluctuations in the wet and dry seasons.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Increased Hydropsychidae density with increased flow fluctuations in the wet season confirms the results of Elliott (1968), Troelstrup and Hergenrader (1990), and Boon (1993). Unlike Hydropsychidae, Simuliidae densities were reduced with increased flow fluctuations in the wet and dry seasons.…”
Section: Discussionsupporting
confidence: 78%
“…Chance and Craig (1986) also reported that Simuliidae larvae had a lower risk of being displaced by moderate flow changes because of their hydrodynamic and morphological adaptations to cling to the substrate, which is much less true for Hydropsychidae. Chironomidae drift densities increased with increased flow fluctuations in both wet and dry seasons, corroborating the results of Irvine and Henriques (1984) but differing from the results of Gislason (1985) and Troelstrup and Hergenrader (1990).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…During the period of highest energy demand, power is generated and water is rapidly released producing much higher and faster flows that fluctuate daily (Jones, 2013). These fluctuating discharges below impoundments may alter benthic invertebrate assemblages downstream, as a result of higher velocities, increased bed instability, and altered water temperature and quality, leading to higher invertebrate drift rates (Troelstrup and Hergenrader, 1990;Bruno et al, 2009;Smokorowski et al, 2011). Flows created by dam operations modulate natural seasonal extremes, and reduce flood frequency, duration and predictability (Poff et al, 1997;Bunn and Arthington, 2002), affecting aquatic biological conditions downstream of dams (Poff and Zimmerman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Large dams reduce river connectivity (Pringle, 2001; Finer & Jenkins, 2012), cause habitat loss (Dudgeon et al, 2006;Freeman, Pringle & Jackson, 2007;Rodrigues & Silva, 2012), alter water temperature and oxygen (Ward & Stanford, 1983;Viana, 2002;Foto Menbohan, Koji, Ajeagah, Bilong Bilong & Njiné, 2012), and interrupt water flow, movement of sediments, nutrients and fauna (Ward & Stanford, 1983;Pringle, 1997;Bunn & Arthington, 2002;Greathouse, Pringle & Holmquist, 2006a;Williams, Armstrong, Katopodis, Lariniere & Travade, 2012). Streams affected by large dams can have decreased macrophyte total biomass, as well as macroinvertebrate abundance, richness, and biomass (Troelstrup & Hergenrader, 1990;Dejalon & Sanchez, 1994;Vinson, 2001). Additionally, due to changes in food sources and substrate, the composition of macroinvertebrate functional groups changes downstream from hydroelectric dams, favoring functional groups that can exploit plankton drifting from the reservoir, and that prefer habitats with low sediment deposition (Dejalon & Sanchez, 1994;Doi et al, 2008;Katano, Negishi, Minagawa, Doi, Kawaguchi & Kayaba, 2009).…”
mentioning
confidence: 99%